Staff Retention in African Universities : Elements of a Sustainable Strategy - Tettey, Wisdom J. (World Bank, Washington, DC, 2021)
The report is organized as follows. It starts with an analysis of the brain drain and its impact on human capacity building. This provides a context for larger issues pertaining to the loss of skilled professionals of which academic staff loss is a sub-category. The discussion helps to demonstrate the similarities in the forces driving these phenomena, and hence the applicability of the recommendations to other organizations, both public and private. This is followed by a discussion of the global problem of academic staff retention and its African manifestations, as we explore the extent of the problem in and its impact on, the continent. The next section reviews the literature on employee retention in order to provide a framework for analyzing the issue of retention in the case study institutions. The report then provides an explanation of the research methodology, findings and discussion, and concludes with some recommendations, examples of good practice, and closing remarks.